Identification and characterization of a novel gene encoding the NBS1 protein in Pyricularia oryzae. Issue 7 (3rd July 2015) - Narukawa-Nara, Megumi; Sasaki, Kengo; Ishii, Akira; Baba, Kouhei; Amano, Kanako; Kuroki, Misa; Saitoh, Ken-ichiro; Kamakura, Takashi
Abstract: The ascomycete Pyricularia oryzae (teleomorph: Magnaporthe oryzae ) causes one of the most serious diseases known as rice blast. The Nijmegen breakage syndrome protein (NBS1) is essential for DNA repair; thus, we studied the P. oryzae NBS1 homolog ( PoNBS1 ). A PoNBS1 null mutant exhibited high sensitivity to DNA damage-inducing agents. The mutant also exhibited the retarded hyphal growth, and induced abnormal conidial germination and shape, but showed normal appressorium formation. The phenotypes of the null mutant were complemented by introducing the cDNA of PoNBS1 driven by a TrpC promoter of Aspergillus nidulans . In addition, the null mutant similarly complemented with the PoNBS1 cDNA lacking the FHA domain that had a normal phenotype except for hyphal growth. These results suggest that PoNBS1 is involved in DNA repair and normal development in P. oryzae. Moreover, the FHA domain of PoNBS1 participates in normal hyphal growth. Abstract: : PoNBS1, a Pyricularia oryzae homolog of the Nijmegen breakage syndrome protein (NBS1) gene, is involved in DNA repair and normal development in P. oryzae.